Role of wild type superoxide dismutase-1 and the effect of mutation on the protein structure and function - Wahab, Mohamad Aminuddin (2016)
Enzyme can give benefit to living things in this world especially human. Enzyme have their own characteristics or more to function that able them to help process in the living things but when mutation happened to the gene of enzyme, the function of enzyme can change and could cause bad side effect to human and could kill the human. Nowadays, there are many research is done in order to understand the mutation that happened. This research project is about the role of Superoxide Dismutase-1 (SOD1) and the mutation that happened on the protein structure of SOD1. The objective of this research project have three objectives that are function of SOD1 enzyme, is compare the wild type of SOD1 and mutated SOD1 gene and last one is to visualize mutated SOD1.